ASISTENSI PELAPORAN SPT TAHUNAN ORANG PRIBADI DENGAN OPTIMALISASI PROGRAM TAX GOES TO CAMPUS - Rudi Harianto; Agustine Dwianika; Irma Paramita Sofia; Fitriyah Nurhidayah; Farhan Ady Pratama (Jurnal Abdi Masyarakat Multidisiplin, 2022)
When the Covid-19 pandemic subsides, many things have been affected in aspects of people's lives and now people's lives are slowly recovering. Starting from lifestyle adjustments in the new normal era, teaching and learning activities both at the school to college level that took place attractively, and government and worker activities began to return to normal. This of course also has an impact on the economic sector, one of which is. Given that public awareness of tax obligations is still relatively low, coupled with the Indonesian economy which was hampered by the pandemic, assistance is needed in reporting the Annual Individual Annual Tax Return. Constraints that are often faced by individual taxpayers in annual personal tax reporting and the existence of a tax payment target from the government (the state), which encourage us to carry out real activities in the form of community service with the Assistance Program for Online SPT Filling (E-Filling) for Individual Taxpayers in the community in South Tangerang. The form of cooperation between the Taxation Center of Pembangunan Jaya University and the Directorate General of Taxes is evident with this activity in the form of the opening of a tax reporting assistance service in March 2022. This activity is given an on-campus tax program where the purpose of this activity is to help the public to report the Annual Individual Tax Return.